Desenvolvimento de equipamento para medir os intervalos R-R - Farah, Leonardo (2015)
This study aimed to develop a device to measure RR intervals, which have high correlation with the values of the gold standard device of electrocardiograph (ECG), by the time domain and frequency domain indices. To this end, a study was conducted with 18 students of Jiu-Jitsu, males with 35.5 ± 8.6 years, at least a weekly frequency of 3 times and one year training. The location was at the academy Gracie Barra de Curitiba PR. They underwent an examination at rest for a period of 7 minutes and then the results were converted into heart rate variability (HRV) and analyzed by the indexes in the time domain and the frequency domain. The results were compared statistically using the Pearson test and intraclass correlation (ICC) and according to them proves to be viable the development of this equipment, which is highly correlated and excellent reproducibility for measuring the RR intervals.